The death of Caesar : the story of history's most famous assassination - Strauss, Barry S. (Simon & Schuster, 2015)
Thanks to William Shakespeare, the death of Julius Caesar is the most famous assassination in history. But what actually happened on March 15, 44 BC is even more gripping than the play. Strauss shows Caesar's assassination was a carefully planned paramilitary operation, put together by disaffected officers and designed with precision. The assassins rallied support among the common people, but they underestimated Caesar's soldiers, who flooded Rome. The assassins were vanquished; their beloved Republic became the Roman Empire.